Urinary phthalate metabolite mixtures in pregnancy and fetal growth: Findings from the infant development and the environment study. (May 2022) - Stevens, Danielle R.; Bommarito, Paige A.; Keil, Alexander P.; McElrath, Thomas F.; Trasande, Leonardo; Barrett, Emily S.; Bush, Nicole R.; Nguyen, Ruby H.N.; Sathyanarayana, Sheela; Swan, Shanna; Ferguson, Kelly K.
Graphical abstract: Abstract: Background: Prenatal phthalate exposure has been linked to reductions in fetal growth in animal and laboratory studies, but epidemiologic evidence is equivocal. Objective: Examine the association between prenatal phthalate metabolite mixtures and fetal growth and evaluate whether that association is modified by fetal sex or omega-3 intake during pregnancy. Methods: Analyses included 604 singleton pregnancies from TIDES, a prospective pregnancy cohort with spot urine samples and questionnaires collected in each trimester. Pregnancy-averaged phthalate exposure estimates were calculated as the geometric means of specific-gravity corrected phthalate metabolites. Fetal growth outcomes included birthweight and length, and ultrasound-derived size and velocity of estimated fetal weight, femur length, abdominal and head circumferences in the second and third trimesters. We used a novel application of quantile g-computation to estimate the joint association between pregnancy-averaged phthalate exposure and fetal growth, and to examine effect modification of that association by infant sex or omega-3 intake during pregnancy. Results: There were few statistically significant differences in birth size and fetal growth by exposure. A one-quartile increase in the phthalate mixture was modestly associated with reduced birthweight (β [95% confidence interval)]: −54.6 [−128.9, 19.7] grams; p = 0.15) and length (−0.2 [−0.6, 0.2] centimeters; p = 0.40). A one-quartile increase in the phthalate mixture was associated with reduced birth length in males (−0.5 [−1.0, 0.0] centimeters) but not for females (0.1 [−0.2, 0.3] centimeters); interaction p = 0.05. The phthalate metabolite mixture was inversely associated with ultrasound-derived fetal growth among those with adequate omega-3 intake. For example, a one-quartile increase in the phthalate mixture was associated with reduced abdominal circumference in the third trimesters in those with adequate omega-3 intake (−3.3 [−6.8, 0.1] millimeters) but not those with inadequate omega-3 intake (1.8 [−0.8, 4.5] millimeters); interaction p = 0.01. Conclusion: Prenatal phthalate exposure was not significantly associated with fetal growth outcomes, with some exceptions for certain subgroups.